KARAKTERISTIK CAMPURAN AC-WC MENGGUNAKAN MATERIAL RECLAIMED ASPHALT PAVEMENT DENGAN TAMBAHAN ASPAL PEN. 60/70 YANG DISUBSTITUSI STYROFOAM - Hendra Arianto; Sofyan M. Saleh; Renni Anggraini (Prodi Magister Teknik Sipil Unsyiah, 2019)
Reuse of reclaimed asphalt pavement material (RAP) is an alternative which applicated for potential enough on the roughness of the road. RAP material can be reused by adding the asphalt and the new aggregate according of the mixture composition so that it is expected will be obtained the quality as planned. One of the efforts made in improving the quality of asphalt mixture RAP material is using a modified asphalt with additional material, such as styrofoam. The use of styrofoam into the asphalt is expected to improve the technical properties of a mixture. The purpose of this research is to know the comparative characteristics of hot mix asphalt (asphalt concrete) type AC-WC that uses RAP material with additional asphalt pen. 60/70 and asphalt pen. 60/70 substitution in the styrofoam by 8%, 10% and 12% against the weight of asphalt based on levels of asphalt left on the material. The initial stages of this study is to conduct an examination of the physical properties of RAP material, then manufacturing a specimen with variations of the addition of asphalt and aggregate new levels based on the job mix diesign (JMD) Bina Marga Aceh (2013). Based on research results, parameter values marshall on all types of asphalt mixture with new aggregate as well as RAP materials and the use of 100% asphalt pen. 60/70 additional or different types of asphalt on OAC has fulfilled the technical specifications defined by the Bina Marga (2014). Best stability values obtained on asphalt mixture using RAP material with additional asphalt pen. 60/70 with 12% styrofoam substitution on OAC JMD Bina Marga Aceh, that amounted to 3,308.72 kg, the lowest value stability retrieved on asphalt mixture using a new aggregate based on the results of Department of Bina Marga Aceh on OAC i.e. of 983.94 kg.